2016
DOI: 10.5194/acp-16-14079-2016
|View full text |Cite
|
Sign up to set email alerts
|

In vitro exposure to isoprene-derived secondary organic aerosol by direct deposition and its effects on <i>COX-2</i> and <i>IL-8</i> gene expression

Abstract: Abstract. Atmospheric oxidation of isoprene, the most abundant non-methane hydrocarbon emitted into Earth's atmosphere primarily from terrestrial vegetation, is now recognized as a major contributor to the global secondary organic aerosol (SOA) burden. Anthropogenic pollutants significantly enhance isoprene SOA formation through acidcatalyzed heterogeneous chemistry of epoxide products. Since isoprene SOA formation as a source of fine aerosol is a relatively recent discovery, research is lacking on evaluating … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 69 publications
(82 reference statements)
4
37
1
Order By: Relevance
“…Aerosol mass concentrations were determined using volume concentrations obtained from SMPS and assuming an aerosol density of 1 g cm −3 . While typical SOA density is about 1.4 g cm −3 , it varies with hydrocarbon precursor identity and reaction conditions, and a density between ∼ 1.0 and 1.6 g cm −3 has been reported in previous studies (Ng et al, 2006(Ng et al, , 2007aChan et al, 2009;Tasoglou and Pandis, 2015;Bahreini et al, 2005). The use of a density of 1 g cm −3 is to facilitate easier comparisons with past and future studies.…”
Section: Aerosol Collection and Extractionmentioning
confidence: 87%
“…Aerosol mass concentrations were determined using volume concentrations obtained from SMPS and assuming an aerosol density of 1 g cm −3 . While typical SOA density is about 1.4 g cm −3 , it varies with hydrocarbon precursor identity and reaction conditions, and a density between ∼ 1.0 and 1.6 g cm −3 has been reported in previous studies (Ng et al, 2006(Ng et al, , 2007aChan et al, 2009;Tasoglou and Pandis, 2015;Bahreini et al, 2005). The use of a density of 1 g cm −3 is to facilitate easier comparisons with past and future studies.…”
Section: Aerosol Collection and Extractionmentioning
confidence: 87%
“…Cloud pH values have been measured at remote locations in the Luquillo Mountains on the Caribbean island of Puerto Rico since 1967. Mean values reported in several studies up through 2012 (Lazrus et al, 1970;Weathers et al, 1988;Asbury et al, 1994;Gioda et al, , 2011Gioda et al, , 2013Reyes-Rodríguez et al, 2009;Valle-Díaz et al, 2016) fall between 4.6 and 5.8, with no apparent trend. The pH values observed and the lack of a clear trend here are consistent with the fairly clean conditions in the region.…”
Section: Recent Observations Of Cloud/fog Ph and Long-term Trendsmentioning
confidence: 90%
“…All in all, except for locations affected by strong haze and specific sources of toxic components (e.g., polycyclic aromatic hydrocarbons (PAHs) and coal combustion in winter in China), a stronger association between PM and mortality was observed at different locations during hotter days, when SOA formation is the most active. Various experiments have also shown that pure SOA does induce adverse effects upon exposure of airway epithelial cells (Arashiro et al, , 2018Gaschen et al, 2010;Lin et al, 2016;Chowdury et al, 2018;Jiang et al, 2016). Similarly, cellular-based ROS assays showed a strong connection with pure SOA or its fraction in PM (Tuet et al, 2016(Tuet et al, , 2017aSaffari et al, 2014).…”
Section: Atmospheric Implicationsmentioning
confidence: 94%